.4(15x-20)=3(3x-4)

Simple and best practice solution for .4(15x-20)=3(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .4(15x-20)=3(3x-4) equation:


Simplifying
0.4(15x + -20) = 3(3x + -4)

Reorder the terms:
0.4(-20 + 15x) = 3(3x + -4)
(-20 * 0.4 + 15x * 0.4) = 3(3x + -4)
(-8 + 6x) = 3(3x + -4)

Reorder the terms:
-8 + 6x = 3(-4 + 3x)
-8 + 6x = (-4 * 3 + 3x * 3)
-8 + 6x = (-12 + 9x)

Solving
-8 + 6x = -12 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-8 + 6x + -9x = -12 + 9x + -9x

Combine like terms: 6x + -9x = -3x
-8 + -3x = -12 + 9x + -9x

Combine like terms: 9x + -9x = 0
-8 + -3x = -12 + 0
-8 + -3x = -12

Add '8' to each side of the equation.
-8 + 8 + -3x = -12 + 8

Combine like terms: -8 + 8 = 0
0 + -3x = -12 + 8
-3x = -12 + 8

Combine like terms: -12 + 8 = -4
-3x = -4

Divide each side by '-3'.
x = 1.333333333

Simplifying
x = 1.333333333

See similar equations:

| f(x)=-0.02x^2+1.4x+5.3 | | 12/5x=4-x | | 2x(x+1)=6(x-4) | | 4k+7h-16=6 | | (3x^2+6x)dx+(x^3+3y^2)dy=0 | | 7/8x3/1 | | -43-2=2-6z | | 3xy+2xy+4= | | X-1/2×5/4=1/12 | | 12/5x=5-x | | X-21=40 | | 6+in(27x)=21-2in(x) | | 9y-6=12 | | x(6x-9)=0 | | 6x-7+4x+7+20x+5=180 | | m-(-13)=36 | | -(8/9)x-(-(8/9)-2) | | -160+9x=60-2x | | 4e(6x+4)=8 | | 2x+30+x+40+2x+75+3x-5=90 | | 2x+30+x+40+2x+75+3x-5=180 | | 2x+30+x+40+2x+75+3x-5=360 | | -7x-32=-11x+56 | | 3/y=12 | | 3+9x=4(x+7) | | -63-4x=21-7x | | 0=5y^2-11y+10 | | x+4.2=1.6 | | 15+3e^2x-7=91 | | -68-2x=-12x+152 | | 2x=8/4 | | x^2+ax+18=0 |

Equations solver categories